“Análisis jurídico y doctrinario a la Ordenanza No. 031-2021 del Gobierno Autónomo Descentralizado del cantón Loja respecto a la determinación y ejecución de sanciones para quienes conducen medios de transporte sostenibles” - Caicedo Morante., Ziare Dallyana (2025)
The rapid growth in the use of electric transportation, such as bicycles, scooters, and electric motorcycles, in the city of Loja creates an urgent need for more sustainable, accessible, and efficient mobility alternatives. This phenomenon, which can be positive from an environmental and economic perspective, presents significant challenges in terms of road safety and urban planning. Poor organization generates risks and conflicts between the different actors who share roads. This research topic covers several topics, including sustainable transportation, administrative sanctions, the principle of proportionality and due process, mobility legislation, public transportation policies, safety features for the use of these sustainable modes, user rights and obligations, the jurisdiction of decentralized autonomous governments, and the promotion of the use of non-polluting transportation. The importance of addressing this issue lies in the need to ensure harmonious coexistence on public roads, where sustainable mobility and user safety are priorities. The lack of clear and adequate regulation creates a gap that impacts not only electric transportation users but also the general public. Regulatory gaps and ambiguity in sanctions jeopardize both security and legal certainty. This study conducted a legal and doctrinal analysis of Ordinance No. 031-2021 of the Decentralized Autonomous Government of the Canton of Loja regarding the determination and execution of sanctions for those who drive sustainable means of transportation. The analysis identified the legal gaps, contradictions, and outdated nature of the ordinance. The analysis and extensive research conducted revealed that the sanctions are not proportional and that a process for enforcing the sanctions committed by offenders is not established. This is a problem because public awareness is lacking and local authorities are unable to exercise their sanctioning powers.